2003
DOI: 10.1021/jf0349026
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on the Photosensitized Isomerization of Bixin

Abstract: The photosensitized isomerization reaction of the natural cis carotenoid bixin (methyl hydrogen 9'-cis-6, 6'-diapocarotene-6, 6'-dioate) with rose bengal or methylene blue as the sensitizer in acetonitrile/methanol (1:1) solution was studied using UV-vis spectroscopy, high-performance liquid chromatography (HPLC), and time-resolved spectroscopic techniques, such as laser-flash photolysis and singlet oxygen phosphorescence detection. In both N(2)- and air-saturated solutions, the main product formed was all-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 34 publications
(64 reference statements)
3
45
0
12
Order By: Relevance
“…As expected, bixin showed lower IC 50 than all annatto extracts. Model studies on the photosensitized isomerisation of bixin show that while bixin in the ground electronic state is stable to thermal isomerization, energy transfer via photosensitization gives rise to the higher energy triplet state precursor, which readily isomerizes to the trans-isomer (Montenegro et al, 2004). Rios et al (2007) showed that bixin, is a very efficient 1 O 2 quencher in fluid solutions due to an efficient energy-transfer process, and confirmed that the triplet state energy level for bixin is lower than that of 1 O 2 (18 kcal mol À1 and 22.5 kcal mol À1 , respectively).…”
Section: Scavenging Of Ros and Rns By Annatto Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, bixin showed lower IC 50 than all annatto extracts. Model studies on the photosensitized isomerisation of bixin show that while bixin in the ground electronic state is stable to thermal isomerization, energy transfer via photosensitization gives rise to the higher energy triplet state precursor, which readily isomerizes to the trans-isomer (Montenegro et al, 2004). Rios et al (2007) showed that bixin, is a very efficient 1 O 2 quencher in fluid solutions due to an efficient energy-transfer process, and confirmed that the triplet state energy level for bixin is lower than that of 1 O 2 (18 kcal mol À1 and 22.5 kcal mol À1 , respectively).…”
Section: Scavenging Of Ros and Rns By Annatto Extractsmentioning
confidence: 99%
“…1), representing approximately 80% of the total carotenoids (Preston & Rickard, 1980). Besides the colorant property, bixin is known to be a very efficient quencher of singlet oxygen ( 1 O 2 ) and triplet state of sensitizers (Montenegro, Rios, Mercadante, Nazareno, & Borsarelli, 2004;Rios, Mercadante, & Borsarelli, 2007). The main phenolic compounds identified in the seeds and/or annatto extracts were hypolaetin and a caffeoyl acid derivative (Chisté, Yamashita, Gozzo & Mercadante, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The carotenoids containing more than seven conjugated double bonds are singlet oxygen quenchers (Di Mascio, Kaiser, & Sies, 1989), can deactivate the triplet excited state of sensitisers responsible for synglet oxygen formation (Montenegro, Rios, Mercadante, Nazareno, & Borsarelli, 2004), and are free radicals scavengers (Bohm, Puspitasari-Nienaber, Ferruzi, & Schwartz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bixin, as almost all carotenoids, is an efficient quencher of singlet oxygen ( 1 O 2 ) (Di Mascio, Kaiser, & Sies, 1989;Montenegro, Rios, Mercadante, Nazareno, & Borsarelli, 2004) due to its triplet energy level of 18 kcal/mol being lower than the energy level of 1 O 2 (Rios, Mercadante, & Borsarelli, 2007). In addition, carotenoids are also able to quench the excited triplet state of sensitizers, which are relevant species in the oxidation of lipids, vitamins and proteins (Montenegro, Nunes, Mercadante, & Borsarelli, 2007;Montenegro et al, 2004).…”
Section: Introductionmentioning
confidence: 99%